Controversies in Ocular Myasthenia Gravis - Evoli, Amelia; Iorio, Raffaele (Frontiers in Neurology, 2020)
Myasthenia gravis (MG) with symptoms limited to eye muscles [ocular MG (OMG)] is a rare disease. OMG incidence varies according to ethnicity and age of onset. In recent years, both an increase in incidence rate, particularly in the elderly, and a lower risk for secondary generalization may have contributed to the growing disease prevalence in Western countries. OMG should be considered in patients with painless ptosis and extrinsic ophthalmoparesis. Though asymmetric muscle involvement and symptom fluctuations are typical, in some cases, OMG can mimic isolated cranial nerve paresis, internuclear ophthalmoplegia, and conjugate gaze palsy. Diagnostic confirmation can be challenging in patients negative for anti-acetylcholine receptor and anti-muscle-specific tyrosine kinase antibodies on standard radioimmunoassay. Early treatment is aimed at relieving symptoms and at preventing disease progression to generalized MG. Despite the absence of high-level evidence, there is general agreement on the efficacy of steroids at low to moderate dosage; immunosuppressants are considered when steroid high maintenance doses are required. The role of thymectomy in non-thymoma patients is controversial. Prolonged exposure to immunosuppressive therapy has a negative impact on the health-related quality of life in a proportion of these patients. OMG is currently excluded from most of the treatments recently developed in generalized MG.